УПРАВЛІННЯ ІННОВАЦІЙНИМ ПОТЕНЦІАЛОМ СУБ’ЄКТА ГОСПОДАРЮВАННЯ В УМОВАХ ЦИФРОВІЗАЦІЇ - Терлецька, Юлія; Заремба, Анастасія (My University, 2025)
Digitalization in the face of modern challenges and threats is a justified and inevitable process of development of a commodity producer, which ensures a high level of competitiveness of an innovative and active business entity. It requires a strategic approach to the process of practical implementation, search and implementation of all types of investments and continuous improvement of the innovative potential of the enterprise. It is the innovative potential and strategies for its practical implementation that are key factors in the successful functioning of a business entity in the conditions of instability of the operating environment.
MANAGEMENT OF THE INNOVATIVE POTENTIAL OF A BUSINESS ENTITY IN THE CONDITIONS OF DIGITALIZATION
Keywords: innovation potential, innovation-active enterprise, digitalization, instability of the operating environment, digital technologies.